COVID-19 and political crisis effects on risk minimising portfolio for Malaysia’s stock markets using MEAN-CVAR optimization model / Amera Katrina Kornain ... [et al.] - Kornain, Amera Katrina; Maasar, Mohd Azdi; Ismanazir, Nur Aisyah Nadhirah; Roseli, Najwa (UiTM Cawangan Negeri Sembilan, 2022)
This research focuses on the effects of the coronavirus disease 2019 (CoVid-19) pandemic and political crisis, onto Malaysia’s (portfolio) stock markets. CoVid-19’s emergence as a pandemic has caused significant impacts on society, corporations, and institutions across the world in many ways. The pandemic has also influencing financial markets and the global economy. This is due to the strict curfews, travel restrictions and border crossing limitations. Throughout the pandemic, Malaysia has also gone through a constitutional crisis that worsen the effects on the stock markets. Modern Portfolio Theory (MPT) is pioneered by Harry Markowitz (1952) model that uses variance to measure risk. Since Markowitz’s work on the theory, optimization has been at the heart of all work relating to portfolio selections. Various mean-risk models are introduced as the results of the Markowitz’s Nobel-prize-winning work (refer Roman and Mitra (2009)). On top of this, various applications of mean-risk models motivated from MPT are being studied recently (see Abdul Razak et al. (2019), Maasar et al. (2016), Maasar et al. (2020), Maasar et al. (2021) for examples).